IMPROVING THE SKILL AND THE INTEREST OF WRITING ADVERTISEMENTS AND POSTERS THROUGH ESA SEQUENCE - Yuniarti, Fatma (JURNAL SMART, 2016)
The action reserach aims at improving the studentsâ writing skill especially to write advertsements and posters. Both are the short functional texts to be learned at the first semester of the ninth grade. According to the data on pre cycle, the students of class IXA Junior High School Swadhipa Natar, South Lampung got difficulties in writing advertisements and posters. A treatment was necessary to help the students overcome their problem. To consider the related literature, the writer decided to implement ESA sequence in the class. The elements of teaching in ESA Sequence are Engage (to arouse the studentsâ interests), Study (learn the language focus), and Activate (use the language freely and communicatively).The data were taken from the test of the linguistic competence mastery, the students writing, and the questionnaire. The result shows ESA Sequence can improve the studentsâ ability in writing advertisements and posters.Key words : ESA (Engange Study Activate), advertisement, poster.